2017
DOI: 10.1001/jamaoncol.2016.6435
|View full text |Cite
|
Sign up to set email alerts
|

Association of Therapy for Autoimmune Disease With Myelodysplastic Syndromes and Acute Myeloid Leukemia

Abstract: In a large population with primary AID, azathioprine exposure was associated with a 7-fold risk for myeloid neoplasm. The control and case cohorts had similar systemic exposures by agent category. No association was found for anti-tumor necrosis factor agents. Finally, no timeline was found for the association of drug exposure with the incidence in development of myeloid neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 28 publications
0
51
1
4
Order By: Relevance
“…A recent study showed that patients under treatment with anti-TNF agents do not have an increased risk for MDS. 25 Detailed literature search did not reveal any association between 5q deletion and methotrexate or TNF-a inhibitors. Finally, despite the fact that the presence of RA and MDS in the same patient could be an incidental co-existence, further investigation might elucidate the possible role of B cells in RA-associated MDS.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that patients under treatment with anti-TNF agents do not have an increased risk for MDS. 25 Detailed literature search did not reveal any association between 5q deletion and methotrexate or TNF-a inhibitors. Finally, despite the fact that the presence of RA and MDS in the same patient could be an incidental co-existence, further investigation might elucidate the possible role of B cells in RA-associated MDS.…”
Section: Discussionmentioning
confidence: 97%
“…NLR is a recognized tool for the assessment of the systemic inflammatory response and has been shown to be affected by VD [25]. Of clinical relevance is the association between MDS and autoimmune disorders that have been reported in several case report studies and long-term follow-up studies [26,27]. Furthermore, two recent epidemiological studies showed that history of infection was significantly associated with a higher risk of developing MDS [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Azathioprine sodium use was observed more frequently in cases, with a 7‐fold risk for myeloid neoplasm. No significant association between a specific length of time of exposure to an agent and the drug's category was observed …”
Section: Registry Studiesmentioning
confidence: 95%
“…A total of 57 out of 86 cases (66.3%) received a cytotoxic or an immunomodulating agent.Azathioprine sodium use was observed more frequently in cases, with a 7-fold risk for myeloid neoplasm. No significant association between a specific length of time of exposure to an agent and the drug's category was observed 105. RESPONSE OF AUTOIMMUNE MANIFESTATIONS TO THERAPIES FOR MDSThe biological interplay existing between the MDS pathogenesis and the development of autoimmune manifestations is somehow mirrored…”
mentioning
confidence: 99%